Flocculation of Azophloxine Using FeCl3 by Ultrasonic Treatment - Zhang, Wenjie; Du, Ling; He, Hongbo (Asian Journal of Chemistry, 2015)
A combination of flocculation with FeCl3 and ultrasonic treatment was explored in decoloration of azophloxine. The results reveal that decoloration rate of the dye increases with increasing amount of FeCl3 used in the solution when FeCl3 amount is less than 15 mg. The decoloration of the dye reaches its maximum value when 15 mg of FeCl3 is added into the solution. The optimal flocculation time is 40 min. The optimum ultrasonic treating time in assisting flocculating of azophloxine is 15 min and the most suitable ultrasonic power to assist flocculating efficiency of FeCl3 is 80 W. Decoloration rate is smaller at higher initial azophloxine concentration.